2016
DOI: 10.1371/journal.pone.0157958
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the Food Manufacturing Chain on the Viability and Functionality of Bifidobacterium animalis through Simulated Gastrointestinal Conditions

Abstract: The viability and functionality of probiotics may be influenced by industrial production processes resulting in a decrease in probiotic efficiency that benefit the health of humans. This study aimed to investigate the probiotic characteristics of Bifidobacterium strains isolated from fecal samples of healthy Thai infants. In the present work, three local strains (BF014, BF052, and BH053) belonging to Bifidobacterium animalis showed a great resistance against conditions simulating the gastrointestinal tract. Am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 53 publications
0
20
0
1
Order By: Relevance
“…animalis subsp. lactis strain BF052, a fecal isolate from healthy infants [ 75 ]. Blast analysis of the 32 spacer regions of L .…”
Section: Resultsmentioning
confidence: 99%
“…animalis subsp. lactis strain BF052, a fecal isolate from healthy infants [ 75 ]. Blast analysis of the 32 spacer regions of L .…”
Section: Resultsmentioning
confidence: 99%
“…Due to the similarity between oxgall and human bile in bile acid composition, oxgall powder, a product derived from bovine bile, has been commonly used to assess the bile tolerance ability of potential probiotic strains at a concentration of 0.3% (wt/vol) instead of human bile [ 14 – 16 ]. In the international literature, the oxgall powders used for bacterial bile tolerance assay were mainly obtained from three manufacturers, namely Sigma-Aldrich (USA) [ 17 , 18 ], Oxoid (UK) [ 19 – 21 ] and BD Difco (USA) [ 22 , 23 ]. Little or no information has been reported on the total bile acid content and the content of the individual bile acids in commercially available oxgall powders.…”
Section: Introductionmentioning
confidence: 99%
“…For example, it has been postulated that osmotic shock or formation of intracellular ice may affect some properties of probiotics. As for freeze drying, whereas no significant differences in the adhesion capability to Caco‐2 cells or in the resistance to simulated gastrointestinal transit of B. animalis BF052 were detected among lyophilized and nonlyophilized cells (Charnchai and others ), du Toit and others () found that freeze drying of probiotics, included B. lactis Bb12, had an effect on adhesion potential, showing an overall significant decrease in the ability of the lyophilized probiotic to exclude, displace, or outcompete certain pathogens. IL‐10 induction was only evident in animals treated with the lyophilized culture in the large intestine.…”
Section: Resultsmentioning
confidence: 97%